Manajemen Sistem Informasi Desa (SID) terhadap Kualitas Pelayanan Publik dan Transparansi Desa Sepit: Village Information System (SID) Management on the Quality of Public Services and Transparency in Sepit Village - Lalu Moh. Fahri; Romi Oriza; Jum’atul Aini; Maulina Intan Fitriani; Dwi Trisna Sekar Nurti (Pendidikan Al-Gafari, 2026)
The village is the smallest government unit that has an important role in providing public services to the community. Along with the development of information technology, village governments are required to increase transparency and efficiency of services through the implementation of the Village Information System (SID). This study aims to analyze the influence of Village Information System (SID) management on improving the quality of public services and government transparency in Sepit Village, Keruak District, East Lombok Regency. The background of this study departs from the challenges faced by village governments in managing data and information efficiently and accountably in the digital era, where SID is one strategic solution. This study uses a quantitative approach with descriptive methods and data collection techniques through observation, questionnaires, interviews, and documentation. The results show that SID management plays a positive role in accelerating village administrative services and increasing public access to information. However, SID implementation has not been optimal due to several obstacles such as limited competency of village officials, inadequate technological infrastructure, and low digital literacy among the community. In addition, village transparency through SID is still not optimal due to minimal data updates and a lack of socialization to the community.